2004
DOI: 10.1128/iai.72.2.833-843.2004
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicansYeast and Germ Tube Forms Interfere Differently with Human Monocyte Differentiation into Dendritic Cells: a Novel Dimorphism-Dependent Mechanism To Escape the Host's Immune Response

Abstract: The ability of Candida albicans to convert from the yeast (Y) form to mycelial forms through germ tube (GT) formation is considered a key feature of the transition of the organism from commensalism to virulence. We show here that human monocytes cultured with granulocyte-macrophage colony-stimulating factor and interleukin-4 (IL-4) after phagocytosis of Y forms did not differentiate into dendritic cells (DCs); they retained CD14, did not acquire CD1a, and were unable to express the maturation markers CD83 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 49 publications
4
20
0
1
Order By: Relevance
“…This response is similar to our findings, in which up-regulated hypha formation associated with mature biofilm formation did not result in any change in IFN-␥ level. Similar results were also reported for interactions between dendritic cells and C. albicans yeast and hyphae (13) and the role of C. albicans in the differentiation of monocytes to dendritic cells (41).…”
Section: Discussionsupporting
confidence: 76%
“…This response is similar to our findings, in which up-regulated hypha formation associated with mature biofilm formation did not result in any change in IFN-␥ level. Similar results were also reported for interactions between dendritic cells and C. albicans yeast and hyphae (13) and the role of C. albicans in the differentiation of monocytes to dendritic cells (41).…”
Section: Discussionsupporting
confidence: 76%
“…In our present study, we found that when live C. albicans was cultured in direct contact with PBMCs at a dose lower than 10 4 /ml, most live C. albicans could be phagocytosed and killed by monocytic phagocytes. However, when live C. albicans was cultured with a concentration higher than 10 5 /ml, C. albicans could escape monocytic phagocytes (28) and form a big hyphae clumping within the culture well, accompanied by increasing cell death through trypan blue staining. To bypass this hurdle, we have successfully adopted a transwell system to avoid the direct contact between live C. albicans and PBMCs and demonstrated that soluble factors released by C. albicans actively modulated cytokine profiles induced by heat-killed C. albicans in PBMCs within 24 h of coculturing (19).…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes that phagocytose C. albicans yeast cells or germ tubes were unable to differentiate into DCs, and internalisation of germ tubes was reported to render cells incapable of inducing Th polarization. 78 Further, the yeast and hyphal forms of C. albicans exert opposing effects on DCs, skewing Th polarization induced both in vitro and in vivo. 79,80 Such a polarization of the cytokine response may function to subvert Th subset differentiation to those which enable fungal persistence within the host.…”
Section: Subversion Of Adaptive Immune Responses By Candida Albicansmentioning
confidence: 99%